Application of Coconut Fibres as Outer Eco-insulation to Control Solar Heat Radiation on Horizontal Concrete Slab Rooftop. (2015) - Mintorogo, Danny Santoso; Widigdo, Wanda K; Juniwati, Anik
Abstract: Many countries alongside equator will experience excessive solar radiation, regardless the top and four sides of the buildings' surfaces. Due to the modern architectural concept and fast growing industry and economic, hundreds of rows of two-to-three-story shops and office houses have been built on the central business districts. Those buildings built are equipped with flat bare and uninsulated concrete rooftop. Only few of flat rooftops are equipped with numerous un-eco-insulation developed in the world such as asphalt roll membranes, single-ply rubber membranes, Ethylene Propylene Diene Monomer (EPDM), and Thermoplastic Polyolefin. This paper deals with the use of coconut fibres to build thermal insulation on concrete slab roofings and the experimental measurements of roof surface and indoor air temperatures derived from dynamic climatology of solar radiation. Monthly average temperatures on rooftop concrete slab and room air temperatures were conducted. Coconut fibres will be considered as natural sustainable insulator with the following aspects: practicing to respect natural materials within the built environment, promoting less harzardus roofing insulation of the material used, limiting the impacts on the urban-built atmosphere, and preserving cooling energy demand by mitigating the flat concrete rooftop thermal onto the room. The room air thermal saving covered by coconut fibres is around 2.8 o – 3.1 o C different, and the rooftop surface thermal saving with coconut fibres is 13 o C different, compared to conventional bare concrete slab roofings. The energy consumption reduction is around 3% (average) and 9% (maximum).